Peripheral Primitive Neuroectodermal Tumor of the Ovary: The Report of Two Rare Cases - Fatemeh Nili; Azadeh Sedighi moghadam pour; Hedieh Moradi Tabriz; Parisa Sedighi Moghadam Pour; Hana Saffar (Iranian Society of Pathology, 2018)
Peripheral primitive neuroectodermal tumor (pPNET) is a highly aggressive small round cell tumor belonging to PNET/Ewing sarcoma family. Ovarian tumors composed of primitive neuroectodermal elements are extremely rare. Herein we reported two cases of peripheral primitive neuroectodermal tumors of ovary in two patients with different clinical presentations. Definite diagnoses were made based on the histomorphology and immunohistochemistry results. With respect to different clinical behaviors, treatment modalities and prognosis of peripheral primitive neuroectodermal tumors compared to other known ovarian neoplasms, it is essential to consider this entity as a differential diagnosis in ovarian tumors especially in young patients.